Response Time Nurses in Providing Services with Patient Satisfaction Installed Emergency Department - Doondori, Anatolia K.; Sekunda, Maria; Cahyani, Sisilia Leny; Kurnia, Theresia A. (JURNAL KESEHATAN PRIMER, 2019)
Background: Patient satisfaction is determined by the service that one of nurse is a fast response time and precise handling. Respon time can reduce the extent of internal organ damage and also suppress the financing burden. The purpose of this research is to determine the correlationship between nursing response time in providing service and patient satisfaction in Emergency Department of Ende General Hospital. Methode: This is a correlational research conduct with cross sectional approach. The sample amount of 130 patients selected in accidental sampling. The instrument used in this research is the watch to calculate response time and a patient satisfaction questionnaire consisting of 21 statements on the desired patient/family expectations and the perceived patient/family statement after Get service at Emergency Department. Result: The results showed that the response time nurse of Ende Publich Hospitall in the fast category so that the patient is satisfied with the service at the IGD RSUD Ende. Analysis results showed there is a link between the response time of nurses in providing service with the satisfaction of patients with a value of P value 0.00. Conclusion: The sooner the time response nurse will provide satisfaction to the patient. Therefore, we need to improve the quality of human resources and facilities in the IGD space to maintain the quality of service.